2010
DOI: 10.1007/s13213-010-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating factors affecting growth and cellular mcyB transcripts of Microcystis aeruginosa PCC 7806 using real-time PCR

Abstract: The effects of temperature and light intensity on Microcystis aeruginosa PCC 7806 growth and mcyB transcripts (as a function of microcystin biosynthesis) were investigated at the logarithmic and stationary growth phases. The expression of the mcyB gene-one of the microcystin biosynthetic genes-under different treatments was quantified using real-time PCR. The results showed that cell number increased at 25°C with all light treatments. A significant positive correlation (P=0.060) between mcyB transcripts and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Several studies supported the relationship between the algal growth rate and the toxin content. 16,22 On the basis of the potency estimation and the ROS inhibition assay, our study speculated that the production of intra-microcystin in M. aeruginosa induced by metalaxyl primary originated from ROS and genetic transcription. A previous study indicated that mcy gene knockout algae were more vulnerable to H 2 O 2 than the normal toxic strain, which indicated a potential relationship between ROS and mcy genes.…”
Section: Resultsmentioning
confidence: 93%
“…Several studies supported the relationship between the algal growth rate and the toxin content. 16,22 On the basis of the potency estimation and the ROS inhibition assay, our study speculated that the production of intra-microcystin in M. aeruginosa induced by metalaxyl primary originated from ROS and genetic transcription. A previous study indicated that mcy gene knockout algae were more vulnerable to H 2 O 2 than the normal toxic strain, which indicated a potential relationship between ROS and mcy genes.…”
Section: Resultsmentioning
confidence: 93%
“…17 Levels of microcystin expression are highly variable according to environmental conditions and individual genotype, and therefore it is possible for a site to have a relatively low concentration of Microcystis yet produce significant amounts of microcystins, or have a high concentration of Microcystis but be nontoxic. 38,39 Microcystis Distribution Patterns. Figure 1 displays the relative proportions of Microcystis abundances across the lake based on qPCR derived total and toxigenic Microcystis cell equivalents from all sampling sites and sampling transects.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Some environmental factors are also known to regulate mcyB transcription. The main one is the light, both its intensity, and its quality (Kaebernick et al, 2000;El Semary, 2010). However, the cyanobacteria we sampled had been buried in the sediments for a long period of time and so in total darkness, and our sampling strategy meant that they were not exposed to light.…”
Section: Discussionmentioning
confidence: 99%